Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1038/aps.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoking in type 2 diabetes development

Abstract: Many patients with type 2 diabetes mellitus (DM2) are at risk for micro and macro vascular complications, which could be observed in heavy smokers. Cigarette smoking increases the risk for type 2 diabetes incidence. Nicotine, acknowledged as the major pharmacologically active chemical in tobacco, is responsible for the association between cigarette smoking and development of diabetes. This minireview summarized recent studies on nicotine effects on insulin action and insulin secretion, indicating the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 35 publications
3
87
0
4
Order By: Relevance
“…This study found that longer durations and higher intensity of smoked tobacco products use were significant risk factors for diabetes among adults in the KSA. This is in agreement with a number of studies which reported that smoking could be independently associated with glucose intolerance, impaired fasting glucose, and development of type 2 diabetes (13)(14)(15)(16)(17)(18)(19)(20)(29)(30)(31)(32). These studies showed a dose-response relationship between smoking and incidence of diabetes, that cigarette smoking is an independent and modifiable determinant of type 2 diabetes mellitus and that smokers who quit may derive substantial benefit from doing so (33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that longer durations and higher intensity of smoked tobacco products use were significant risk factors for diabetes among adults in the KSA. This is in agreement with a number of studies which reported that smoking could be independently associated with glucose intolerance, impaired fasting glucose, and development of type 2 diabetes (13)(14)(15)(16)(17)(18)(19)(20)(29)(30)(31)(32). These studies showed a dose-response relationship between smoking and incidence of diabetes, that cigarette smoking is an independent and modifiable determinant of type 2 diabetes mellitus and that smokers who quit may derive substantial benefit from doing so (33).…”
Section: Discussionsupporting
confidence: 91%
“…However, smoking as a risk factor for type 2 diabetes mellitus was reported from many recent international studies (13)(14)(15)(16)(17)(18)(19)(20). These cohort and cross-sectional studies suggest that smoking may be an independent and modifiable risk factor for the development of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies reported that smoking was associated with lower weights and BMI [11][12][13]. Smoking is also known to be associated with insulin resistance and type 2 diabetes [14][15][16]. To further study the relationship between smoking status and obesity in Saudi civilians, we performed a cross-sectional population-based study of Saudi adults, with multiple indicators such as BMI, age, sex and smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…Nakashita et al 29 in cross-sectional study with Japanese subjects, found a prevalence of 5.1% in cigarette smokers. Studies indicate that tobacco use has been associated with reduced insulin sensitivity and development of in-sulin resistance 28 , promoting glucose metabolism disorders, leading to hyperglycemia 14 .…”
Section: Discussionmentioning
confidence: 99%
“…cortisol 12,13 . In addition, chronic smokers are at increased risk for developing insulin resistance and inadequate compensatory response of insulin secretion, which promotes the association of smoking with an increased risk of type 2 diabetes mellitus 14 .…”
mentioning
confidence: 99%